STUDENTS’ ERROR IN CONSTRUCTING PASSIVE VOICE - Impiani Zagoto; Restu Damai Laia (Jurnal Education and Development, 2021)
Passive is considered as one of the important aspects in English grammar that should be mastered by the leaner. In fact, however, most of the students make some mistakes that can be considered as the errors since it happens regularly. Hence, this research tried to find out the students’ error in constructing the passive sentence. The qualitative-explanative design was used to describe the students’ error. The data gathered through documentary technique was analyzed by using Miles and Huberman’s interactive model that is data reduction, data display and then verifying or drawing conclusion. The result of data analysis showed that there were two types of students’ errors in constructing the passive, namely past participle error and auxiliary error.